Uniqueness of Urbanization in the USSR: Artificial Formation of the Settlement System - Meerovich, Mark (project baikal, 2015)
All urbanization processes in the USSR were quite different from those in other countries. When the industrialization started, all new cities were built far from the existing big cities, which served as supporting points of displacement of population within the framework of the Soviet town-planning doctrine. The pre-revolutionary structure of economic zoning was purposefully replaced by a new one, where ‘industrial-residential’ formations – the places of nodal conglomeration of population – were deliberately located in the area favorable for allocation of war productive facilities. The Soviet government willfully turned urbanization into ‘an involuntary companion’ of industrial and transport construction and resource development. It remained such as long as the Soviet Union existed.
Keywords: urbanization in the USSR; social city; administrative-territorial zoning; war productive facilities